Karakterisasi berbagai Jenis Bahan Lapisan Kedap, Ketebalan dan Nisbah Bentonit dengan Pasir: Konsep Dasar Pengelolaan Lahan Pasir Pantai - Saparso, Saparso; Tohari, Tohari; Shiddieq, Dja’far; Setiadi, Bambang (JOURNAL OF TROPICAL SOILS, 2009)
Characterization of Various Kinds, Thickness and Bentonite Sand Ratio as Hardplain Materials: a Basic Concept for Coastal Sandy Land Management (Saparso, Tohari, D. Shiddieq, and B. Setiadi): Coastal sandy land development faces the sand characteristics, the lower holding water capacity and the larger nutrient leaching due to heavier rainfall in the tropics, soil porosity and without soil layering so it need alternative technology for more efficient harvesting water resources in supporting the crop growing. The laboratory research studied the characteristic of various kind, thickness and ratio of hardplain material was carried out at Laboratory of Agronomy of UNSOED, Soil Mechanic of GMU. the SEM and X-RD of Lemigas Jakarta. Permeability determination by Falling Head which is appropriate measurment was not significantly different with ELE28-290 permeameter. Permeability of Kokap clay soil and Nanggulan bentonite were larger than the rainfall intensity in coastal sandy land. The Sentolo Vertisol content 68% calcium smectite had permeability 3,7 mm.day-1. Bentonite permeability were not significantly different due to more than 80% clay mineral composition. Therefore the permeability of natrium bentonite like as BPIB and BLUB namely 1.4 x 10-2 and 10-2 mm day-1 were lower than the calcium bentonite like as RMBL and BLBK permeability namely 4.3 x 10-2 and 2.43 x 10-2 mm day-1. Permeability of 0.5 cm thickness bentonite was not significantly different than 1.0 dan 1.5 cm thickness and those had very low permeability. Bentonite sand mixture 15 and 20 percent produced bentonite sand agregate that had mesopores by which allowing the drainage and available soil water so that those had water permeability 13.7 dan 10.3 mm day-1 respectively. The mixture 30-100% had not significantly different permeability namely 7.3 x 10-2 up to 1.4 10-2 mm day-1. The combination of tickness and the low ratio of bentonite sand mixutre need to be determined to produce favourable environment in supporting the plant growth.